Comparative pH analysis of synthetic and natural cleaning agents: implications for eco-friendly and dermatological safety - Chaudhary, Narendra Kumar; Yadav, Mandip; Budhathoki, Sujan; Baral, Dipak; Adhikari, Janak; Bhattarai, Ajaya (BIBECHANA, 2025)
Cleaning agents are essential for maintaining hygiene in domestic and industrial settings, and their pH plays a critical role in determining their safety and efficacy. This study analyzed the pH profiles of synthetic (soaps, shampoos, and detergents) and natural cleaning agents (Aloe vera and Reetha) in dilute solutions to evaluate their implications for skin health and environmental safety. The results showed that soaps like Neem Kanti Patanjali and No. 1 exhibited near-neutral to mildly alkaline pH (6.88–7.95), making them suitable for skin applications, whereas shampoos such as Dove and Sunsilk displayed slightly acidic profiles (6.35–6.85), aligning with the scalp’s natural pH. Detergents, including Surf Excel and Ariel, were strongly alkaline (8.16–8.59), indicating effective cleaning but potential harshness on sensitive skin. Natural agents demonstrated eco-friendly properties, with Aloe vera being mildly acidic (5.40–5.79) and Reetha being near-neutral to slightly alkaline (7.36–7.74). Dilution reduced alkalinity or acidity across all samples, emphasizing the importance of proper usage of concentrations. These findings highlight the need for pH-balanced formulations to ensure compatibility with human skin and minimize environmental harm. Future research should focus on optimizing product formulations for skin health, biodegradability, and ecological safety while promoting sustainable cleaning practices.